GoodGovUX: Improving the User Experience of Federal Government Digital Products Through Public-Private Collaboration. (September 2016) - Deaven, Keith; Kabel, Margo; Sun, Norm; Pass, Jeff; Stoner, Jason; Gartland, Emily
The mission of GoodGovUX is: "to drive the adoption of a common set of UX best practices within the government agency and government contracting communities." The initiative is an effort between private and public sector UI/UX professionals to drive conversation, and more importantly, action, between the private and public sectors to improve the user experience of government-owned web and digital properties. The group consists of working teams focused on three key areas of improvement: terminology and definitions, the Request for Proposal (RFP) process, and standards and best practices. The Terminology and Definitions Team is primarily focused on consolidating and defining the myriad of words and phrases that are unique to the UX profession. The goal of this effort, in addition to simply getting everyone speaking the same language, is to allow for non-UX professionals to author portions of RFP's to better request UX services. In concert, the RFP Team is working to ensure UX is a critical consideration of any RFP that contains digital properties that users will need to interact with. They are integrated into the TechFAR process, and are creating tools to help RFP authors better recognize the need for, and incorporate, UX requirements. The focus of the Standards and Best Practices Team is to provide resources to guide the improvement of UX deliverables, and to facilitate a conversation around industry best practices. Currently under development is a decision support tool to assist users in determining UX best practices for a given topic and providing links to examples. Future deliverables from this team could be aggregating and showcasing examples of excellent UX work, partnerships with other government agencies to drive standards (i.e., USDS and their digital style guide) and other initiatives geared toward the specifics of UX quality and methodology. The discussion by this panel will center on the GoodGovUX effort, and progress made to date, in the context of the changing UX landscape within the government and private sector. The panel will engage the audience for feedback and suggestions for improvement, give the audience a chance to participate in the overall effort, and facilitate a general Q&A session on the state of UX within the federal government. The panel will consist of UX professionals from both the public and private sectors, representing each of the working teams. Each of the panelists has a unique perspective on the evolution of UX and its intersection with digital government.